The ProtecT trial: analysis of the patient cohort, baseline risk stratification and disease progression. (12th February 2020) - Bryant, Richard J.; Oxley, Jon; Young, Grace J.; Lane, Janet A.; Metcalfe, Chris; Davis, Michael; Turner, Emma L.; Martin, Richard M.; Goepel, John R.; Varma, Murali; Griffiths, David F.; Grigor, Ken; et al.
Abstract : Objective: To test the hypothesis that the baseline clinico‐pathological features of the men with localized prostate cancer (PCa) included in the ProtecT (Prostate Testing for Cancer and Treatment) trial who progressed ( n = 198) at a 10‐year median follow‐up were different from those of men with stable disease ( n = 1409). Patients and Methods: We stratified the study participants at baseline according to risk of progression using clinical disease stage, pathological grade and PSA level, using Cox proportional hazard models. Results: The findings showed that 34% of participants ( n = 505) had intermediate‐ or high‐risk PCa, and 66% ( n = 973) had low‐risk PCa. Of 198 participants who progressed, 101 (51%) had baseline International Society of Urological Pathology Grade Group 1, 59 (30%) Grade Group 2, and 38 (19%) Grade Group 3 PCa, compared with 79%, 17% and 5%, respectively, for 1409 participants without progression ( P < 0.001). In participants with progression, 38% and 62% had baseline low‐ and intermediate‐/high‐risk disease, compared with 69% and 31% of participants with stable disease ( P < 0.001). Treatment received, age (65–69 vs 50–64 years), PSA level, Grade Group, clinical stage, risk group, number of positive cores, tumour length and perineural invasion were associated with time to progression ( P ≤ 0.005). Men progressing after surgery ( n = 19) were more likely to have a higher Grade Group and pathological stage at surgery, larger tumours, lymph node involvement and positive margins. Conclusions: We demonstrate that one‐third of the ProtecT cohort consists of people with intermediate‐/high‐risk disease, and the outcomes data at an average of 10 years' follow‐up are generalizable beyond men with low‐risk PCa.